LITERARY LANGUAGE AND ITS NORMS IN THE LESSONS OF THE RUSSIAN LANGUAGE (LITERATURE) - Mirzakulov Uktam Alimardanovich (Zeta Repository, 2023)
This article shows the problems faced by a teacher who conducts classes in the Russian language (literature). In this article, the author of the article spoke about literary language and artistic language, the teacher tried to explain to students in the process of passing literature lessons how to distinguish between one and the other, that is, the difference between the literary language and the artistic language. This article proves that the two languages are different from each other.